PENGARUH AKUNTABILITAS, TRANSPARANSI DAN SISTEM AKUNTANSI KEUANGAN DESA TERHADAP PENGELOLAAN KEUANGAN DESA (Studi Kasus Pada Desa Ulupulu: Kecamatan Nangaroro, Kabupaten Nagekeo) - Hermanus Reo; Yuliana Sedho (JSE: Jurnal Sharia Economica, 2025)
The aim of the research is to determine the influence of Accountability, Transparency and Village Financial Accounting Systems on Village Financial Management in Ulupulu Village, Nangaroro District, Nagekeo Regency. The type of research used in this research is quantitative research. In this study, a multiple linear regression model test was used. The sampling technique in this research was purposive sampling where the sample determined by the researcher was 94 respondents consisting of the people of Ulupulu village, Nangaroro subdistrict, Nagekeo district who had criteria determined by the researcher. Primary data and secondary data are used by researchers to test several variables, where related data is collected through questionnaire techniques. The research results show that accountability influences village financial management. The test results show that the coefficient value (β) of the Accountability variable is 0.185 with tcount > ttable (2.105 > 1.98667) and a significant level of 0.038 < 0.05. Transparency influences Village Financial Management. The test results show that the coefficient value (β) of the Transparency variable is 0.209 with tcount > ttable (2.127 > 1.98667) and a significance level of 0.036 < 0.05. The Village Financial Accounting System influences Village Financial Management. The test results show that the coefficient value (β) of the Village Financial Accounting System variable is 0.196 with tcount > ttable (2.022 > 1.98667) and a significant level of 0.046 < 0.05.